Intelligent Surveillance Drone System for Health Care Enhancement in a Smart City - Melhim, Loai Kayed B. (Communications in Mathematics and Applications, 2023)
Accelerating medical services to provide appropriate health care within the available time is essential, especially in critical cases. Achieving this goal depends on the response speed of the health care teams in reaching the accident scene and the people who are seeking or needing health care services. Response speed depends entirely on the data provided to these teams by the requesters of these services. This work utilizes drone technologies through a set of developed algorithms to ensure the provision of the required data in the shortest possible time. Drones fly for a specific time to carry out the required tasks over a specified area. The area of interest is divided into a group of zones, and a set of drones is allocated to each zone. The provided algorithms will minimize the maximum completion time required to perform all assigned tasks for all regions. Practical experiments were performed using two classes of 280 different instances to assess the performance of the developed algorithms; different criteria were used to measure the performance of these algorithms. The obtained results showed the ability of the presented algorithms to achieve the assumed goal by reducing the maximum completion time. Results showed that the best algorithm is MCZ with a percentage of 100% and a 0.00 average gap.